Effects of early neonatal proinflammatory stress on the expression of BDNF transcripts in the brain regions of prepubertal male rats - D. I. Peregud; S. V. Freiman; A. O. Tishkina; L. S. Sokhranyaeva; N. A. Lazareva; M. V. Onufriev; M. Y. Stepanichev; N. V. Gulyaeva (Вавиловский журнал генетики и селекции)
Early postnatal proinflammatory stress provokes behavioral impairments in adulthood; however, underlying mechanisms are still elusive. Brain-derived neurotrophic factor (BDNF) plays a crucial role in neuroplastic changes in health as well as at pathology. The BDNF gene is transcribed to exon-specific mRNAs and the pattern of their expression depends on stimulus. We suggest that disturbances of exonspecific BDNF mRNA expression in the brain regions after stress induced by proinflammatory stimuli in early postnatal period could be one of the underlying mechanisms of consequent behavioral impairments. Thus, the aim of the study was to investigate the effects of proinflammatory stress in early postnatal ontogeny on the expression of BDNF and the patterns of expression of the BDNF gene in the neocortex and hippocampus of prepubertal male rats. The proinflammatory stress was induced by subcutaneous administration of bacterial lipopolysaccharide (LPS) to rat pups on postnatal days 3 and 5, while BDNF expression was analyzed in 36-day-old rats. BDNF polypeptide concentration was estimated by means of an enzyme-linked immunosorbent assay, while quantitative polymerase chain reaction followed by reverse transcription was used to detect exon-specific BDNF mRNA expression. The levels of BDNF and transcripts, containing common exon IX were similar in the control and LPS-treated rats. In the rats treated with LPS, the level of BDNF mRNA, containing exon IV, was lower in the neocortex, but not in the hippocampus. No changes in the expression of the transcripts containing exons I and VI were observed in any brain structure studied. We suggest that specific alterations in BDNF expression may be involved in the susceptibility to the development of behavioral impairments of animals subjected to early proinflammatory stress.